1989
DOI: 10.1002/eji.1830191008
|View full text |Cite
|
Sign up to set email alerts
|

B cell repertoire in adult antigen‐free and conventional neonatal balb/c mice

Abstract: Early in ontogeny B cells preferentially use VH gene families which are most adjacent to the genes coding for the constant part of the immunoglobulin molecule. In conventional adult mice, however, a random usage of VH gene families has been found. We investigated the role of exogenous antigenic stimulation on this normalization of VH gene usage by B cells. Therefore, we made use of adult germ-free BALB/c mice fed a chemically defined ultrafiltered antigen-free diet (GF-CD) and neonatal conventional BALB/c mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This process must be absent in germ-free mice, since their VH family repertoires mimic those of neonatal BALB/c (10,11,29). We found that the administration of isologous immunoglobulins from normal adult mice was able to selectively diminuish the usage of the VH7183 family in germ-free mice.…”
Section: Discussionmentioning
confidence: 78%
“…This process must be absent in germ-free mice, since their VH family repertoires mimic those of neonatal BALB/c (10,11,29). We found that the administration of isologous immunoglobulins from normal adult mice was able to selectively diminuish the usage of the VH7183 family in germ-free mice.…”
Section: Discussionmentioning
confidence: 78%
“…In mice, only a small fraction of this potential repertoire seems to be expressed as functional antibody (2). Utilization of this repertoire appears to be developmentally regulated in a strain-specific fashion (3)(4)(5) with subsequent modification by environmental stimuli (7).…”
mentioning
confidence: 99%
“…The genes from VH families located at the 3' end of the VH locus are preferentially expressed in pre-B, neonatal, and germ-free adult B-cell repertoires (33,34). A similar bias is also seen in the VH repertoire of autoreactive B cells (35).…”
mentioning
confidence: 88%